Identifikasi Sektor Ekonomi Kreatif Sebagai Sarana Pendukung Perkembangan Desa Wisata Di Desa Beng, Kecamatan Gianyar, Kabupaten Gianyar - Purba, Biancha Capricornia; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA, 2024)
The research entitled "Identification of Creative Economy Sectors as Means to Support the Development of a Tourism Village in Beng Village, Gianyar Subdistrict, Gianyar Regency" is a qualitative descriptive study that utilized one informant as the data source. The aim of this research is to identify the creative economy sectors that play a role in supporting the development of a Tourism Village in Beng Village, Gianyar Subdistrict, Gianyar Regency. Beng Village has been designated as a Tourism Village by the local government, and the creative economy has significant potential to enhance the village's economy and sustainability. The research employed survey and interview methods with craftsmen, artists, and business owners in the village. The findings indicate that the dominant creative economy sectors in Beng Village are the production of Barong Clothes, Weaving, and the culinary industry of Babi Guling (Roast Suckling Pig). These three sectors contribute significantly to job creation, income improvement, and the promotion of tourism in the village. However, challenges faced in the development of the creative economy in Beng Village include price competition, product quality enhancement, and effective marketing. Therefore, collaboration among creative economy stakeholders, government support, and skills development are necessary to strengthen the creative economy sector in Beng Village. This research provides a better understanding of the potential and challenges in the development of the creative economy in a tourism village. Keywords: Creative Economy, Tourism Village, Culinary, Fashion.